Encountering suffering in digital care: a qualitative study of providers' experiences in telemental health care - Jill W. Åhs; Albertine Ranheim; Henrik Eriksson; Monir Mazaheri (BMC, 2023)
Abstract Background Encountering patients who are suffering is common in health care, and particularly when providing mental health care. Telehealth technologies are increasingly used to provide mental health care, yet little is known about the experiences of providers when encountering patients who are suffering within remote care. The present study explored health care providers' lived experiences of encountering patient suffering during telemental health care. Methods A qualitative phenomenological approach was used to uncover participants' experiences. In-depth interviews were conducted with a purposive sample of physicians, psychologists, and therapists who used telemental health in varied clinical practices in Sweden. Data were analyzed using descriptive phenomenology. Results Telehealth care with patients who were suffering was experienced by providers as loose connections, both literally in compromised functioning of the technology and figuratively in a compromised ability connecting emotionally with patients. Providers' lived experiences were explicated into the following aspects: insecurity in digital practice, inaccessibility of the armamentarium, and conviction in the value of telehealth care. Interpersonal connection between patient and provider is necessary. Worry and guilt arose for providers with fears that technology would not work, patient status was deteriorated, or the care needed could not be delivered. Providers overcame barriers in telehealth encounters, and expressed they perceived that patients appreciated the care received, and through it found relief. Conclusions This study brings an understanding of experiences in providing telemental care for patients who are suffering. Providers experience challenges in connecting with patients, and in accessing tools needed to enable reaching the goals of the caring encounter. Efforts to ensure functioning of technology, comfort with its use, and accessibility of tools might be some accommodations to support providers for successful and rewarding telehealth care encounters.